2017
DOI: 10.1159/000455062
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Failure and Mortality in Hemodialysis Patients with Tunneled Cuffed Venous Catheters in a Single Center

Abstract: Background: As of now, only a few studies have focused on the failure of tunneled cuffed venous catheter (tCVC) and mortality of hemodialysis (HD) patients using tCVC as long-term vascular access, whose vascular condition for arteriovenous fistula was not very satisfactory. In this study, we aimed to provide information about the first tCVC failure and survival rates of patients in this population. Methods: Fifty-nine patients who used tCVC from January 1, 2009 to December 31, 2014 in our HD center were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
(25 reference statements)
4
6
3
2
Order By: Relevance
“…However, some studies have described median catheter patency >300 days . Moreover, Shi et al reported extremely good catheter survival (median catheter survival for TCC, 45.0 months) . However, that study had only a few subjects, excluded bridge VA, and the age of subjects was younger than in our study.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…However, some studies have described median catheter patency >300 days . Moreover, Shi et al reported extremely good catheter survival (median catheter survival for TCC, 45.0 months) . However, that study had only a few subjects, excluded bridge VA, and the age of subjects was younger than in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Low catheter survival in our study was because all catheter removal (including planned catheter removal) or death of the catheter was analyzed as an event. The incidence of catheter‐related infection has been reported as 0.3–1.0 per 1000 patient days . We observed a relatively low incidence of catheter‐related infection and the incidence did not differ between the early phase and late‐phase groups.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…As taxas de sobrevida de cateter observadas neste estudo estão abaixo da maioria dos trabalhos encontrados na literatura, apesar de não haver estudo que compare especificamente os CCP e CTLP. Mandolfo et al 16 encontraram uma sobrevida cumulativa de CTLP de 91% em 1 ano e de 85% em 4 anos, enquanto Shi et al 17 observaram sobrevida de 82% em 1 ano e de 42% em 4 anos. Por outro lado, Shingarev et al 14 descreveram taxas de perviedade de cateteres bem Tabela 3.…”
Section: Discussionunclassified